Agricultural integrated living skills teachers' receptivity to assessment for learning practices in Malaysian secondary schools - Mat Rashid, Abdullah; How, Shwu Pyng (Center for Promoting Ideas, 2019)
This study employed a cross-sectional survey research design to determine the receptivity to assessment for learning practices among Agricultural Integrated Living Skills (ILS) teachers in Malaysian secondary schools. The instrument used is a set of questionnaire which engaging Agricultural ILS teachers in secondary schools of Malaysia as samples. The purpose of this study specifically focused on the level of teacher receptivity and its difference towards assessment for learning practices among Agricultural ILS teachers in Malaysian secondary schools. The findings shows that the level of Agricultural ILS teachers’ receptivity to assessment for learning practices were mostly at the moderate level in secondary schools. Furthermore, there are significant differences in assessment for learning practices among Agricultural ILS teachers in regards to the level of receptivity. Several recommendations are made based on the findings especially for the improvement of teacher receptivity to assessment for learning practices in schools.